Design of the Advance Directives Cohort: a study of end-of-life decision-making focusing on Advance Directives - Onwuteaka-Philipsen Bregje D; Kaspers Pam J; Pasman H; Rurup Mette L; van Wijmen Matthijs PS (BMC, 2010)
Abstract Background ADs are documents in which one can state one's preferences concerning end-of-life care, aimed at making someone's wishes known in situations where he/she is not able to do so in another manner. There is still a lot unclear about ADs. We designed a study aimed at investigating the whole process from the formulating of an AD to its actual use at the end of life. Methods/Design The study has mixed methods: it's longitudinal, consisting of a quantitative cohort-study which provides a framework for predominantly qualitative sub-studies. The members of the cohort are persons owning an AD, recruited through two Dutch associations who provide the most common standard ADs in the Netherlands, the NVVE (Right to Die-NL), of which 5561 members participate, and the NPV (Dutch Patient Organisation), of which 1263 members participate. Both groups were compared to a sample of the Dutch general public. NVVE-respondents are more often single, higher educated and non-religious, while amongst NPV-respondents there are more Protestants compared to the Dutch public. They are sent a questionnaire every 1,5 year with a follow-up of at least 7,5 years. The response rate after the second round was 88% respectively 90% for the NVVE and NPV. Participants were asked if we were allowed to approach close-ones after their possible death in the future. In this way we can get insight in the actual use of ADs at the end of life, also by comparing our data to that from the Longitudinal Aging Study Amsterdam, whose respondents generally do not have an AD. Discussion The cohort is representative for people with an AD as is required to study the main research questions. The longitudinal nature of the study as well as the use of qualitative methods makes it has a broad scope, focusing on the whole course of decision-making involving ADs. It is possible to compare the end of life between patients with and without an AD with the use of data from another cohort.